The past, current and future trends in DNA vaccine immunisations - Sidgi Syed Anwer Abdo Hasson; Juma Khalifa Zayid Al-Busaidi; Talal Abdulmalek Sallam (Asian Pacific Journal of Tropical Biomedicine, 2015)
This review focuses on DNA vaccines, denoting the last two decades since the early substantiation of preclinical protection was published in Science in 1993 by Ulmer et al. In spite of being safely administered and easily engineered and manufactured DNA vaccine, it holds the future prospects of immunization by inducing potent cellular immune responses against infectious and non-infectious diseases. It is well documented that injection of DNA plasmid encoding a desired gene of interest can result in the subsequent expression of its products and lead to the induction of an immune response within a host. This is pertinent to prophylactic and therapeutic vaccination approach when the peculiar gene produces a protective epitope from a pathogen. The recent studies demonstrated by a number of research centers showed that these immune responses evoke protective immunity against several infectious diseases and cancers, which provides adequate support for the use of this approach. We attempt in this review to provide an informative and unbiased overview of the general principles and concept of DNA vaccines technology with a summary of a novel approach to the DNA vaccine, present investigations that describe the mechanism(s) of protective immunity provoked by DNA immunization and to highlight the advantages and disadvantages of DNA immunisation.